MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA DALAM MENGUNGKAP SEJARAH PENYIARAN AGAMA BUDDHA DENGAN MEDIA INTERAKTIF DALAM PEMBELAJARAN AGAMA BUDDHA SISWA KELAS VIII SMP NEGERI 2 PEKANBARU - Kaad Kaad (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This classroom action research aims to increase students' interest and motivation in the subjects of class VIII Buddhism inSMP Negeri 2 Pekanbaru. This research is a classroom action research with the research subjects are Class VIII studentswho are Buddhists, amounting to 9 people including 8 men and 1 woman. Techniques for collecting data through written testtechniques. The results showed that the Buddhist learning outcomes of students experiencing improvement in the first cycle ofmeeting 1 obtained an average score of 72.7. At meeting 2 it increased to 77.0. In the second cycle the meeting 1 increased to75.8. And at meeting 2 it increased to 77.8.